Album Prefaces and Other Documents on the History of Calligraphers and Painters - Thackston, Wheeler (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This volume contains album prefaces in the original Persian version with English translation, miscellaneous documents relating to calligraphers and painters, and specimens of travel literature from the Timurid and Safavid periods.